Influence of olanzapine on memory functions - Ružić, Klementina (Array, 2009)
Even though memory dysfunction is not considered to be a diagnostic criterion for schizophrenia, results of a neuropsychological research indicate significant damage in mnestic functioning, especially in verbal memory (Saykin et al. 1991). This type of a disorder is recorded in patients with a first episode of schizophrenia, as well as in chronic patients (Saykin et al. 1994). These researches show that this deficit is not influenced by neuroleptics. Paulsen and associates suggest that the deficit of verbal learning in schizophrenia is related to difficulties in encoding retrieving information without significant storage (rapid forgetting) problems (Paulsen at al. 1995). We will present a case of a 36 - year old male who is suffering from a paranoid schizophrenia